Novel 16, 17-epoxy-23-methylergostane derivative from Sinularia variabilis, a soft coral from the Persian Gulf, with apoptotic activities against breast cancer cell lines. Issue 15 (1st August 2022) - Mohammadi Pour, Pardis; Yegdaneh, Afsaneh; Aghaei, Mahmoud; Ali, Zulfiqar; Khan, Ikhlas A.; Ghanadian, Mustafa
Abstract: The steroidal and terpenoidal composition of Sinularia variabilis was investigated by chromatography methods. One new (1 ), and four known [gorgasta-5-en-3β-ol (2 ), ergosta-5-en-3β-ol (3 ), ergosta-5, 22( Z )-dien-3β-ol (4 ), 5, 8-epidioxy-5α, 8α-ergosta-6, 22E-dien-3β-ol (5 )] steroids, in addition to one known diterpenoidal alkaloid [sinulasulfone (6 )] isolated for the first time from S. variabilis . If we named the 23-methylergostane core structure as sinustane, new compound (1 ) was elucidated as 16α, 17α-epoxysinusta-5-en-3β–ol-20β-yl sulfate based on NMR and HR Mass data. It was submitted for cytotoxic activity evaluation against MCF-7 and MDA-MB-231 cell lines using MTT assay. Apoptosis induction was checked by flow cytometry (annexin V/propidium iodide) staining. To determine the production of reactive oxygen species, and the mitochondrial transmembrane potential (ΔΨm), the DCFDA, and JC‐1 probes were used in this study. Graphical Abstract: UF0001